The effect of various endodontic irrigants on the sealing ability of Biodentine and other root perforation repair materials (In vitro study) - Ahmed K Al-Zubaidi; Abdul Karim J Al-Azzawi (College of Dentistry/ University of Baghdad, 2014)
Background: This in vitro study was carried out to evaluate the effect of various endodontic irrigants (sodium hypochlorite, ethylene diaminetetracetic acid and normal saline) on sealing ability of (Biodentine, mineral trioxide aggregate, and amalgam) used to repair furcal perforations. Material and methods: One hundred and twenty extracted human molars with divergent roots were used in this study. A standard root canal access cavity was prepared in each tooth and furcal perforation was made and was standardized by using k file size 100 instrument to get a perforation of (1.32mm) in diameter .The teeth were randomly divided in to three groups of 40 teeth according to the type of material used to repair the perforations (Group A: The furcal perforations were repaired with Biodentine, Group B: The furcal perforations were repaired with MTA ,Group C: The furcal perforations were repaired with Amalgam). Each group was then subdivided into 4 subgroups according to irrigation regimens applied over the repair site (Subgroup 1: without irrigation, Subgroup 2: the pulp chamber was gently irrigated with 10 mL 5.25% Sodium hypochlorite for 10 minutes, Subgroup 3: Pulp chamber was gently irrigated with 10 mL 17% Ethylene Diaminetetracetic acid for 10 minutes, Subgroup 4: pulp chamber was gently irrigated with 10 mL normal saline for 10 minutes. Each tooth was coated with two layers of nail varnish and then sticky wax except 1 to 2 mm around the perforation site. Each tooth was placed in glass vial containing 3 ml of buffered Methylene blue dye at (37°C, pH 7) and kept in an incubator for 72 hour at 100% humidity. After dye application, the teeth were washed in running water for 5 min. Each tooth was sectioned longitudinally in a buccolingual direction. Results: The results showed that group A has least mean of dye penetration and the difference was highly significant with group C and non-significant with group B.Saline and NaOCl increase the sealing of all groups while EDTA significantly increased the dye penetration of Biodentine and MTA respectively. Conclusions: Biodentine has the best sealing ability of the tested materials while amalgam showed the highest dye penetration of all tested materials. Saline and NaOCl increase the sealing ability of Biodentine and MTA where as EDTA decreased the sealing efficacy of MTA and Biodentine.